Production of Adipic Acid from Mixtures of Cyclohexanol-Cyclohexanone using Polyoxometalate Catalysts - Lesbani, Aldes; Sumiati,; Mardiyanto,; Fithri, Najma Annuria; Mohadi, Risfidian (UI Scholars Hub, 2015)
Adipic acid production through catalytic conversion of cyclohexanol-cyclohexanone using polyoxometalate H5[a-BW12O40] and H4[a-SiW12O40] as catalysts was carried out systematically. Polyoxometalates H5[a-BW12O40] and H4[a-SiW12O40] were synthesized using an inorganic synthesis method and were characterized using Fourier transform infrared spectroscopy (FTIR). Adipic acid was formed from conversion of cyclohexanol-cyclohexanone and was characterized by using melting point measurement, identification of functional group using FTIR spectrophotometer, analysis of gas chromatography-mass spectrometry (GC-MS), and 1H and 13C NMR (nuclear magnetic resonance) spectrophotometer. This research investigated the influence of reaction time and temperature on the conversion. The results showed that adipic acid was formed successfully with a yield of 68% by using H5[a-BW12O40] as the catalyst with a melting point of 150-152 °C after optimization. In contrast, using H4[a-SiW12O40] as the catalyst, the formation was only 3.7%. Investigation of time and temperature showed 9 h as the optimum reaction time and 90 °C as the optimum temperature for conversion of up to 68%. Identification using FTIR, 1H, and 13C NMR showed that the adipic acid from conversion of cyclohexanol-cyclohexanone was in agreement with the standard adipic acid data in the literatures. GC-MS analysis indicated that several by-products were formed in conversion of cyclohexanol-cyclohexanone using H5[a-BW12O40] and H4[a-SiW12O40] as the catalysts.